Simplify 3/10x + 1/6y + 3/10x + 3/6y. Be sure to reduce any fractions to the lowest terms.

5 answers

To simplify 3/10x + 1/6y + 3/10x + 3/6y, we can combine like terms. The x terms are already like terms, so we can add them together: 3/10x + 3/10x = 6/10x = 3/5x.

The y terms are also like terms, so we can add them together: 1/6y + 3/6y = 4/6y = 2/3y.

Therefore, the simplified expression is 3/5x + 2/3y.
Simplify 9x + 3y − 6 − 5x + 4y −3.
To simplify 9x + 3y - 6 - 5x + 4y - 3, we can combine like terms.

9x - 5x = 4x
3y + 4y = 7y
-6 - 3 = -9

Therefore, the simplified expression is 4x + 7y - 9.
Simplify 12e − 5f − 7e +3f
To simplify 12e - 5f - 7e + 3f, we can combine like terms.

12e - 7e = 5e
-5f + 3f = -2f

Therefore, the simplified expression is 5e - 2f.